Daylighting technology for energy efficiency and thermal comfort for Wilayah Mosque in Kuala Lumpur / Abdul Halim Othman - Othman, Abdul Halim (2002)
My Final Project course under Prof. Dr. Azni Zain Ahmed is to perform a field evaluation and an analysis of energy efficiency by using daylighting technology as the main source of illumination and as a replacement for the usage of conventional artificial light due to energy savings at the Wilayah Mosque, Jalan Duta, Kuala Lumpur. The efficiency of the daylight illumination and indoor thermal comfort, which spread out in the prayer hall for prayer activities, reading and gathering is the main objective of my analysis. My methodology is to measure indoor illumination by using lux meter for direct and global illumination, indoor thermal comfort such as relative humidity, temperature, wind speed by using RH meter, thermocouple and anemometer. This evaluation and analysis were performed at the main prayer hall only. From my analysis it was found that the daylighting system functioned efficiently to ligl1t up most of the entire prayer hall. This illumination level was within the accepted level and more than enough for religious activities following Malaysia Standard MS 1525:2001 (page 16). It was found that air conditioning system provided good level of relative humidity due to human comfort for sweat evaporation process but the temperature was too cold. New settings of air condition temperature are needed to provide better condition for any religious activities.